TAWASSUT ATTITUDE RELEVANCE NAHDLATUL ULAMA IN PREVENTING EXTREMISM - Munandar, Siswoyo Aris; Kubro, Ummu Azizatul (IAIN Palangka Raya, 2021)
What was currently happened is the legitimacy of violence, which justified theologically as the term jihad fī sabīlillāh. Radicalisms believed and felt they had the right to commit acts of violence in the name of religion and God. In facts, what they were doing was violating religious rules and staying away from God. The attitude of tasawuf and tawassut in Nahdlatul Ulama prevented radicalism. Based on the background of the problems described above, the study focused on how was the concept of tawassut and tasawwuf in preventing radicalism movements? The purpose was to find out the meaning of tawassuf in Nahdlatul Ulama and to describe the concept of tawassut and tasawwuf